α1-adrenoceptors and takotsubo syndrome: pathophysiologic connotations : authors’ reply - Huang, Mengying; El-Battrawy, Ibrahim; Zhou, Xiao-Bo; Akın, Ibrahim (Europace, 2021)
We appreciate the interest of Dr Madias in our paper entitled ‘Alpha 1 adrenoceptor signaling contributes to toxic effects of catecholamine on electrical properties in human-induced pluripotent stem cell derived cardiomyocytes’.1We agree with Dr Madias about the illustrated points.2 Regarding receptors involved in takotsubo syndrome (TTS), we also believe that beta- and alpha-adrenoceptors must play some role in the pathogenesis of TTS. The role and mechanisms of beta-receptor activation in the toxic effect of catecholamine excess have been investigated in numerous studies using various models, including human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). The contribution of beta-adrenoceptors to TTS has been well established. Although alpha-receptors in cardiomyocytes have a lower density than beta-receptors, they can also possibly contribute to TTS to a certain extent. Our paper only attempts to emphasize the role of alpha receptors in this scenario and does not underscore the importance of beta-receptors in TTS.
Im Titel ist die "1" bei "α1-adrenoceptors" tiefgestellt
Gesehen am 28.06.2022